Breaking news production processes in US metropolitan newspapers: Immediacy and journalistic authority. (January 2018) - Usher, Nikki
Incremental updates to breaking news stories online have become embedded in newspapers in the 24/7 online era. This article reviews four US metropolitan newspapers, using field observations and interviews to examine how journalists choose breaking news stories and their rationale for these continuous updates. Specifically, the article explores the connection between temporality and authority, positing that journalists use these updates to retain their role as authoritative truth-tellers in relation to audiences, the competition, and their own position in the profession. As newspaper coverage becomes more like local TV, these metropolitan newspaper journalists worry that a breaking news strategy, while potentially necessary, is also questionable and even potentially harmful, but nonetheless pursue it.